2021
DOI: 10.1007/s42452-020-03988-1
|View full text |Cite
|
Sign up to set email alerts
|

Banana pseudostem substitution in wheat flour biscuits enriches the nutritional and antioxidative properties with considerable acceptability

Abstract: Biscuits prepared from composite flours substituted with unconventional plant resources have been considered important for enriching the overall nutritional quality. The present study was undertaken to explore the potential of banana pseudostem flour for the valorization of wheat flour biscuits. At the same time, the study attempts to address the problem of bioresource wastage as huge amounts of banana pseudostem are wasted every year after harvesting of the fruits. In this study, composite flours were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…The decrease in ash content of biscuit samples over time may be related to moisture absorption, which reduces the concentration of other components. These conclusions are supported by the finding of Chakraborty et al ( 55 ). Mineral losses can be caused by reducing sugars reacting chemically with proteins or amino acids under the influence of heat to produce compounds that bind minerals.…”
Section: Resultssupporting
confidence: 80%
“…The decrease in ash content of biscuit samples over time may be related to moisture absorption, which reduces the concentration of other components. These conclusions are supported by the finding of Chakraborty et al ( 55 ). Mineral losses can be caused by reducing sugars reacting chemically with proteins or amino acids under the influence of heat to produce compounds that bind minerals.…”
Section: Resultssupporting
confidence: 80%
“…When medicinal applications of banana peel are discarded after harvesting, they are also not usually utilized in food production [4] pointing out that the production of food products from by-products can become better for the nutritional value of them. [5] are benefitted in getting great into the utilization of byproducts like a banana peel. It is a great medicinal application of banana peel containing high amounts of various nutrients that have been used to produce massive food products.…”
Section: Introductionmentioning
confidence: 99%
“…According to Deng et al (2020), BPS has a significant number of metabolites, particularly flavonoids, phenolic acids, amino acids, and alkaloids. As reported by Chakraborty et al (2021), polyphenols and flavonoids such as ferulic acid, catechin, gingerol, and cinnamic acid have antioxidant properties. revealed that pseudo-stems also showed antimicrobial and antitumor properties.…”
Section: Banana Pseudo-stemmentioning
confidence: 73%
“…According to researchers, fortification of BPS in biscuits resulted in an increase in their protein, antioxidants, phytochemicals (flavonoids, phenols, alkaloids, tannins, and ascorbate) and ash content while decreasing their fat, moisture content, and viscosity compared to that of the control wheat flour biscuits (Chakraborty et al, 2021). Biscuits produced using BPSs provide a nutrient‐rich product, particularly in terms of potassium, calcium, sodium, ash, fat, and fiber content (Maskey et al, 2020).…”
Section: Applications Of Banana and Its By‐products In Food Industrymentioning
confidence: 99%